Low Physical Activity and High Screen Time Can Increase the Risks of Mental Health Problems and Poor Sleep Quality among Chinese College Students - Wu, Xiaoyan; Tao, Shuman; Zhang, Yukun; Zhang, Shichen; Tao, Fangbiao (PLOS ONE, 2015)
Objective To test the independent and interactive associations of physical activity (PA) and screen time (ST) with self-reported mental health and sleep quality among Chinese college students. Method Data were collected in October, 2013. The gender, age, residential background, body mass index (BMI), perceived family economy and perceived study burden were obtained from a total of 4747 college students (41.6% males and 58.4% females). The outcomes were self-reported PA status, ST, anxiety, depression, psychopathological symptoms and sleep quality. Analyses were conducted with logistic regression models. Results Overall, 16.3%, 15.9% and 17.3% of the students had psychological problems, such as anxiety, depression and psychopathological symptoms, respectively. The prevalence of poor sleep quality was 9.8%. High ST was significantly positively associated with anxiety (OR=1.38, 95%CI: 1.15-1.65), depression (OR=1.76, 95%CI: 1.47-2.09), psychopathological symptoms (OR=1.69, 95%CI: 1.43-2.01) and poor sleep quality (OR=1.32, 95%CI: 1.06-1.65). High PA was insignificantly negatively associated with anxiety, depression, psychopathological symptoms and poor sleep. Low PA and high ST were independently and interactively associated with increased risks of mental health problems and poor sleep quality (p<0.05 for all). Conclusion Interventions are needed to reduce ST and increase PA in the lifestyles of young people. Future research should develop and measure the impacts of interventions and their potential consequences on sleep, health, and well being.